Desain Pembelajaran Kerucut Berkonteks Tradisi Megono Gunungan - Nursyahidah, Farida; Saputro, Bagus Ardi; Albab, Irkham Ulil (Jurnal Elemen, 2021)
Geometry is an essential subject for students. However, geometry, especially the cone, remains a challenging material for students. Besides, we need the proper media and context for learning mathematics on cone material. This research aims to develop a learning trajectory that utilizes the Megono Gunungan tradition as a context in the learning process using the Indonesian Realistic Mathematics Education (PMRI) approach. The research method used is Design Research, which consists of three phases of the study: preliminary design, experimental design, and retrospective study. This study's outcome is designing a learning trajectory on cone material using the Megono Gunungan tradition. This learning trajectory comprises four activities, including observing the interactive video of the Megono Gunungan tradition to discover cone elements, finding the concept surface area of a cone using origami paper, and grasping the cone concept volume with magic seeds, and solving contextual problems related to the cone. Studies have shown that using the Megono Gunungan context could help students improve their understanding of the cone concept. Furthermore, this study hoped could be an inspiration for exploring another local wisdom that can be a context in learning mathematics.